2018
DOI: 10.1186/s12889-018-6167-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of physical activity and sedentary behavior among children and adolescents in Shanghai, China: do gender and age matter?

Abstract: BackgroundThere is limited evidence for the prevalence of the co-existence of physical activity (PA) and sedentary behavior (SED), and its correlates among children and adolescents. This study has two aims: 1) to investigate the prevalence of PA and SED, and their co-existence, and 2) to examine the associations between PA or SED, or both with gender and age among children and adolescents in Shanghai, China.MethodsUsing a cross-sectional study design (conducted from September to December 2014), 50,090 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 56 publications
(104 reference statements)
9
47
0
Order By: Relevance
“…The present research indicated that only approximately 20% of adolescents participated in the recommended level of PA (60 minutes of moderate to vigorous PA daily [4]), indicating a lower level of PA among adolescents. This result is consistent with the previously published studies of a regional nature [31,32]. Nevertheless, in contrast with the nationally representative surveys in China [30], the PA level established in the present study is lower.…”
Section: Interpretations Of Ndingssupporting
confidence: 92%
See 2 more Smart Citations
“…The present research indicated that only approximately 20% of adolescents participated in the recommended level of PA (60 minutes of moderate to vigorous PA daily [4]), indicating a lower level of PA among adolescents. This result is consistent with the previously published studies of a regional nature [31,32]. Nevertheless, in contrast with the nationally representative surveys in China [30], the PA level established in the present study is lower.…”
Section: Interpretations Of Ndingssupporting
confidence: 92%
“…This reduced level is potentially explained by the varying measures adopted, which possibly produced inconsistencies in terms of estimating the amount of PA. Concerning the level of ST among adolescents in this study, our level is in accordance with studies based on Chinese adolescent samples [30][31][32]. Despite the ST level exceeding 60%, limiting ST is a necessary mission for the promotion of adolescent health.…”
Section: Interpretations Of Ndingssupporting
confidence: 89%
See 1 more Smart Citation
“…The current research in this area of inquiry in China has focused on pre-school [7] or elementary-aged children [13,21], and no studies, to the knowledge of the authors, have examined proportions of adolescents meeting these health-related guidelines in China. Adolescence may be a particularly important age to examine, given that health-related behaviors become more volitional and less dictated by parents as children grow older [11,22] and the risk for pediatric obesity rises with age [1,23]. Thus, the primary purpose of this observational, cross-sectional analysis was to examine the proportions of adolescents in an eastern province in China who partially or fully meet the PA, screen-time, and sleep duration guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Sociodemographic variables may influence the types of activities that youth choose, as well as barriers they experience when engaging in health-related behaviors. Gender, in particular, may be of particular relevance, given that several studies examining movement guideline adherence among children in China [22], as well as other contexts [12,19], have demonstrated that a lower proportion of girls than boys tend to meet these recommendations together and in isolation. This may be an important point in China, where evidence suggests that girls are at a higher risk of experiencing pediatric obesity than boys [10,24].…”
Section: Introductionmentioning
confidence: 99%